Vowel change across time, space, and conversational topic: the use of localized features in former mining communities. (October 2019) - Devlin, Thomas; French, Peter; Llamas, Carmen
Abstract: This study focuses on speakers who continue to use forms that are recessive in a community, and the phonological and conversational contexts in which recessive forms persist. Use of a local, recessive form is explored across males from four ex-mining communities in Northeast England. Older speakers, who lived in the area when the mines were open, frequently produce the localized variant of the mouth vowel, especially in speech produced during conversation about the locally resonant topic of mining, and, most frequently, in communities closest to the location with which the form is associated. Conversely, speakers born since the loss of mining and with little connection to the industry hardly produce the local form in any community or conversational topic. Exploring conversational topic provides evidence for the connections between shifting social contexts and sound change, specifically that speakers retain otherwise recessive features in speech concerning topics which are locally resonant to them.